Lymphoma Immune Reconstitution Inflammatory Syndrome in the Center for AIDS Research Network of Integrated Clinical Systems Cohort. (21st April 2014) - Gopal, Satish; Patel, Monita R.; Achenbach, Chad J.; Yanik, Elizabeth L.; Cole, Stephen R.; Napravnik, Sonia; Burkholder, Greer A.; Mathews, W. Christopher; Rodriguez, Benigno; Deeks, Steven G.; Mayer, Kenneth H.; Moore, Richard D.; et al.
Abstract : In a multicenter cohort, unmasking immune reconstitution inflammatory syndrome (IRIS) was observed in 12% of HIV-associated lymphomas. Presentation and survival for lymphoma IRIS were similar to non-IRIS, with possibly increased early mortality among IRIS cases. Abstract : Background.  Lymphoma incidence is increased among human immunodeficiency virus (HIV)–infected individuals soon after antiretroviral therapy (ART), perhaps due to unmasking immune reconstitution inflammatory syndrome (IRIS). Clinical characteristics and survival for unmasking lymphoma IRIS have not been described. Methods.  We studied lymphoma patients in the Centers for AIDS Research Network of Integrated Clinical Systems (CNICS) from 1996 until 2011. Unmasking lymphoma IRIS was defined as lymphoma within 6 months after ART accompanied by a ≥0.5 log10 copies/mL HIV RNA reduction. Differences in presentation and survival were examined between IRIS and non-IRIS cases. Results.  Of 482 lymphoma patients, 56 (12%) met criteria for unmasking lymphoma IRIS. Of these, 12 (21%) had Hodgkin lymphoma, 22 (39%) diffuse large B-cell lymphoma, 5 (9%) Burkitt lymphoma, 10 (18%) primary central nervous system lymphoma, and 7 (13%) other non-Hodgkin lymphoma. Median CD4 cell count at lymphoma diagnosis among IRIS cases was 173 cells/µL (interquartile range, 73–302), and 48% had suppressed HIV RNA <400 copies/mL. IRIS cases were similar overall to non-IRIS cases in histologic distribution and clinical characteristics, excepting more frequent hepatitis B and C (30% vs 19%, P = .05), and lower HIV RNA at lymphoma diagnosis resulting from the IRIS case definition. Overall survival at 5 years was similar between IRIS (49%; 95% confidence interval [CI], 37%–64%) and non-IRIS (44%; 95% CI, 39%–50%), although increased early mortality was suggested among IRIS cases. Conclusions.  In a large HIV-associated lymphoma cohort, 12% of patients met a uniformly applied unmasking lymphoma IRIS case definition. Detailed studies of lymphoma IRIS might identify immunologic mechanisms of lymphoma control.